THE OPTIMISM OF JULIA STANFORD IN SIDNEY SHELDON'S MORNING, NOON AND NIGHT: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WIBOWO , RAINDRI (2007)
The major problem of this study is to elucidate the optimism of Julia Stanford reflected in Sydney Sheldon's Morning, Noon and Night. The objectives of the study are; to analyze the structural elements of the novel and to analyze the character of Julia Stanford based on individual psychological perspectives. In conducting this study, the researcher uses qualitative research in which the data are based on primary data, the novel Sydney Sheldon's Morning, Noon and Night itself. While secondary data are Sydney Sheldon's biography and other data which deal with the research. In analyzing the data, she applies some approaches. Firstly, structural analysis approach is used to analyze the elements of the novel. It consists of characterization, setting, point of view, plot, style and theme. Secondly, the individual psychological approach is used for analyzing the optimism of Julia Stanford that influences her daily activity and behavior toward life. These approaches are applied in order to get the appropriate analysis and answer the problems. The writer finds that Julia's optimistic feeling lead her to an autonomous personality that has a great self confident in life.